ANALISIS ISI NILAI MORAL PANCASILA PADA FILM 5 CM - Sidabariba, Nike Erika P; Purwanti, Angel (SCIENTIA JOURNAL, 2021)
Film is a form of mass media. The 5 cm film directed by Rizal Mantovani is based on a novel it self was released on December 12, 2012 which was written by Donny Dhirgantoro. The storyline that carries the theme of friendship with adventure stories, a sense of nationalism and also the moral values of Pancasila as well as dialogues with poetic nuances, the novel has succeeded in reprinting twenty-five times. The film, which was released in 2012, describes how they truggle with the character they dream of, namely the peak of Mahameru. The formulation of the problem how to analyze the content of Pancasila moral values in the film 5 cm. the research method is a qualitative descriptive method with data analysis techniques, namely qualitative content analysis. The results of this study indicate that for “the moral massage of Pancasila that appears” in the film entitled “5 cm” is the moral in human relations with God in the form of belief in God. Morals in human relations with other human beings are kindship, caring, help. Moral in human relations with oneself in the form of fear, honesty, patience, selfishness, courage, self-esteem, pride, doubt and disappointment. Moral in human relations with other human in the form of love, willing to sacrifice, kindship, caring, mutual cooperation and help. Moral in human relations with nature in the form of nature. Everything that happen with nature is related to behavior.